Development and characterization of xyloglucan-poly(vinyl alcohol) hydrogel membrane for Wireless Smart wound dressings. (September 2018) - Ajovalasit, Alessia; Caccami, Maria Cristina; Amendola, Sara; Sabatino, Maria Antonietta; Alotta, Gioacchino; Zingales, Massimiliano; Giacomazza, Daniela; Occhiuzzi, Cecilia; Marrocco, Gaetano; Dispenza, Clelia
Graphical abstract: Highlights: Biocompatible hydrogel dressings for wound remote monitoring are being developed. Hydrogels absorb simulated body fluids up to four times their initial weight. Significant morphological rearrangements occur upon swelling. A step increase in electric conductivity upon fluid uptake above 20% is observed. The hydrogel hydration level affects the response of the integrated RFID tag antenna. Abstract: Hydrogel-based smart wound dressings that combine the traditional favourable properties of hydrogels as skin care materials with sensing functions of relevant biological parameters for the remote monitoring of wound healing are under development. In particular, lightweight, ultra-high frequency radiofrequency identification (UHF RFID) sensor are adjoined to xyloglucan-poly(vinyl alcohol) hydrogel films to battery-less monitor moisture level of the bandage in contact with the skin, as well as wireless transmit the measured data to an off-body reader. This study investigates the swelling behavior of the hydrogels in contact with simulated biological fluids, and the modification of their morphology, mechanical properties, and dielectric properties in a wide range of frequencies (10 0 –10 6  Hz and 10 8 –10 11  Hz). The films absorb simulated body fluids up to approximately four times their initial weight, without losing their integrity but undergoing significant microstructural changes. We observed relevant linear increases of electric conductivity and permittivity with the swelling degree, with an abrupt change of slope that is related to the network rearrangements occurring upon swelling.